2005
DOI: 10.1097/01.qai.0000139398.38236.4d
|View full text |Cite
|
Sign up to set email alerts
|

Improved Obstetric Outcomes and Few Maternal Toxicities Are Associated With Antiretroviral Therapy, Including Highly Active Antiretroviral Therapy During Pregnancy

Abstract: Data from 2543 HIV-infected women were analyzed to correlate antiretroviral therapy (ART) used during pregnancy with maternal and pregnancy outcomes. ART was analyzed according to class of agents used and according to monotherapy versus combination ART containing neither protease inhibitors (PIs) nor nonnucleoside reverse transcriptase inhibitors versus highly active ART. Timing of ART was classified according to early (recorded at or before 25-week gestation study visit) and late (recorded at 32-week gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
115
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 23 publications
9
115
2
5
Order By: Relevance
“…In studies that have examined the relationship between HAART or ZDV monotherapy use during pregnancy, HAART was associated with a higher risk of stillbirth 14, 20, 21. Tuomala et al.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that have examined the relationship between HAART or ZDV monotherapy use during pregnancy, HAART was associated with a higher risk of stillbirth 14, 20, 21. Tuomala et al.…”
Section: Discussionmentioning
confidence: 99%
“…Felizmente, as alterações mitocondriais são raras, mas o seu prognóstico é extremamente desfavorável. Dos efeitos fetais indesejáveis referentes ao uso dos inibidores da protease, os mais relatados são a prematuridade e a restrição de crescimento intra-útero 21,22 , mas existem discordâncias 23 . Recentemente, foi relatada também a ocorrência de insulinopenia neonatal em crianças nascidas de mães que utilizaram estes fármacos durante a gravidez 24 .…”
Section: Identificação De Gestantes Portadoras Do Hiv-1unclassified
“…Dentre os efeitos colaterais maternos decorrentes do uso dos anti-retrovirais são citadas as alterações gastrointestinais, hepáticas, pancreá-ticas e anemia 21 . Adicionalmente, com o uso dos inibidores da protease observam-se as dislipidemias e as alterações sobre o metabolismo glicídico, tanto experimental quanto em gestantes, predispondo ao diabetes gestacional 25,26 .…”
Section: Identificação De Gestantes Portadoras Do Hiv-1unclassified
See 1 more Smart Citation
“…Several large studies from the USA have not found an association between HAART and PTD [90,91]. In two further studies, one multicentre study from the Pediatric Spectrum of HIV Disease cohort and one single-centre study, an association between PTD and HAART was found only if HAART included a PI [92,93].…”
Section: Hiv Protease Inhibitor Therapy and Preterm Deliverymentioning
confidence: 99%